RELATIONSHIP BETWEEN INVENTORY MANAGEMENT POLICIES AND SUPPLY CHAIN PERFORMANCE OF RETAIL SUPERMARKETS IN NAIROBI CITY COUNTY IN KENYA. - Mkonu, Audilia Mkamburi; Gichana, Dr. James Ongwae (International Journal of Supply Chain and Logistics, 2019)
Purpose: To explore the relationship between inventory management policies and supply chain performance of supermarkets in Nairobi City County in Kenya. The study specifically sought to examine the relationship between inventory control policies, risk management policies, information technology policies, and stakeholder management policies and supply chain performance of retail supermarkets in Nairobi City County in Kenya. The study's theoretical review was based on the Balanced Score Card, Contingency theory, Resource Based View and Stakeholder theory. Methodology: Descriptive research design which employed both qualitative and quantitative approaches was used to investigate the relationship between inventory management policies and supply chain performance. The target population was 112 supermarkets in Nairobi City County as listed in the 2016 master file of the Nairobi City County licensing department. Stratified random sampling was used to determine the study sample of 88 using Slovin's sample size formula. Primary data was collected through questionnaires that were administered to supermarkets' supply chain managers by drop and pick technique. Statistical Package for Social Scientists (SPSS) version 21 was used to code, enter, process and analyze data into descriptive and inferential statistics. Results:The study's response rate was 84.1%. Pearson correlation Coefficient (r) and multiple regression models were used to determine the relationship between the study variables. ANOVA was also used to test the significance level of the independent variables on the dependent variable at 95% confidence level. The regression model study results had an adjusted R2 value of 0.672 which showed that the independent variables in the study were able to explain 67.2% variation in supply chain performance with the remaining 32.8 % being explained by other variables outside the model. The study findings established that a positive significant relationship exists between inventory management policies and supply chain performance of retail supermarkets in Nairobi City County in Kenya. Contribution to policy and practice: The study recommended that supermarkets supply chain managers to periodically assess their inventory management policies to ensure that they were effective and adequate in controlling inventory levels and the associated inventory risks while regulating the use of information technology and supporting stakeholder management policies that encourage good relations, timely payment to suppliers, employee efficiency and customer loyalty.